A new method of estimating scapular orientation during various shoulder movements: A comparison of three non-invasive methods. (February 2019) - Matsumura, Aoi; Ueda, Atsushi; Nakamura, Yasuo
Abstract: The conventional acromion marker cluster (AMC) method used to estimate scapular orientation cannot adequately represent complex shoulder movements due to soft tissue artifacts. The regression method may have nonlinear error changes depending on humeral elevation angle and elevation plane. Therefore, we aimed to develop a new method of estimating scapular orientation using curved surface interpolation during various shoulder movements, and to compare its accuracy with conventional and regression methods. Thirteen healthy men were recruited. AMC and refractive markers for bony landmarks were placed on the skin. During the preprocess, several shoulder postures, including different arm elevations and elevation planes, were measured using the motion capture system. Premeasured data were used to calibrate the positional relationship between AMC and scapula using curved surface interpolation. Subsequently, scapular orientations were estimated by measuring AMC and body markers of any shoulder posture. To evaluate the accuracy of our methods, 25 elevation postures and six tasks involving postures common to activities of daily living were applied. For tasks requiring greater arm elevation angles, the root mean square error was less in our method than in the conventional and regression methods. Therefore, our method could improve the accuracy of estimating scapular orientation in various elevation postures.